2013
DOI: 10.1007/s11357-013-9606-z
|View full text |Cite
|
Sign up to set email alerts
|

The anti-aging effects of Ludwigia octovalvis on Drosophila melanogaster and SAMP8 mice

Abstract: We investigated the anti-aging effects of Ludwigia octovalvis (Jacq.) P. H. Raven (Onagraceae), an extract of which is widely consumed as a healthful drink in a number of countries. Using the fruit fly, Drosophila melanogaster, as a model organism, we demonstrated that L. octovalvis extract (LOE) significantly extended fly lifespan on a high, but not a low, calorie diet, indicating that LOE may regulate lifespan through a dietary restriction (DR)-related pathway. LOE also attenuated age-related cognitive decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 65 publications
2
46
0
Order By: Relevance
“…The presence and activation of AMPK is of major importance for both lipid and glycogen synthesis and storage, as well as for the maintenance of gut function, at least in larvae (34). AMPK is probably also responsible for the utilization of triglycerides, leading to energy supply in the adult fly (35).Furthermore, a reduction in AMPK functionality lowers triglyceride stores and diminishes locomotor activity, stress resistance and survival in adult flies (35,(59)(60)(61). Various inducible Drosophila AMPK knockdown strains even show premature larval lethality (61).…”
Section: Discussionmentioning
confidence: 99%
“…The presence and activation of AMPK is of major importance for both lipid and glycogen synthesis and storage, as well as for the maintenance of gut function, at least in larvae (34). AMPK is probably also responsible for the utilization of triglycerides, leading to energy supply in the adult fly (35).Furthermore, a reduction in AMPK functionality lowers triglyceride stores and diminishes locomotor activity, stress resistance and survival in adult flies (35,(59)(60)(61). Various inducible Drosophila AMPK knockdown strains even show premature larval lethality (61).…”
Section: Discussionmentioning
confidence: 99%
“…We found ten studies on flavonoids and lifespan studies in D. melanogaster. Three of them used single compounds such as the flavanol epicatechin and the flavonol fisetin (58)(59)(60) , the other seven studies were on cocoa powder, green tea extract, Ludwigia octovalvis extract, apple polyphenols, black tea extract (BTE) and BE (61)(62)(63)(64)(65)(66)(67) (Table 2).…”
Section: Flavonoids and The Lifespan Of Drosophila Melanogastermentioning
confidence: 99%
“…We recommend this published review to readers and will expand upon Lessing’s and Bonini’s work by discussing dAMPK-related research published during or after 2010. As stated earlier, we will focus on recent studies that demonstrate the protective role of dAMPK with regard to life span and neurodegeneration (Lin et al 2014; Ng et al 2012; Pimenta de Castro et al 2012; Ulgherait et al 2014). …”
Section: 2 Selected Disease Models Studied In Drosophilamentioning
confidence: 99%
“…In agreement with this observation, a second lab has shown that increased pan-neuronal dAMPK activity extends adult female life span (Ulgherait et al 2014). Furthermore, genetic knockdown of dAMPK-α (in the fat body) has been shown to prevent the increased life span induced by β-sitosterol, a natural product that promotes AMPK phosphorylation in Drosophila S2 cell culture (Lin et al 2014). In light of these 3 lines of evidence, it may be tempting to simply conclude that life span positively correlates with dAMPK activity in flies.…”
Section: 2 Selected Disease Models Studied In Drosophilamentioning
confidence: 99%
See 1 more Smart Citation